Dijet Azimuthal Decorrelations in Pp Collisions at ?s=7tev - Karapınar, Güler; Karapınar, Güler; Demir, Durmuş Ali; Demir, Durmuş Ali (American Physical Society, 2011)
Measurements of dijet azimuthal decorrelations in pp collisions at √s=7TeV using the CMS detector at the CERN LHC are presented. The analysis is based on an inclusive dijet event sample corresponding to an integrated luminosity of 2.9pb-1. The results are compared to predictions from perturbative QCD calculations and various Monte Carlo event generators. The dijet azimuthal distributions are found to be sensitive to initial-state gluon radiation. © 2011 CERN, for the CMS Collaboration.
Keywords: Azimuthal decorrelations; Gluon radiation; Integrated luminosity; Quantum Chromodynamics (QCD); Monte Carlo event generators